2015
DOI: 10.12659/msm.894971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sugammadex on Postoperative Bleeding and Coagulation Parameters After Septoplasty: A Randomized Prospective Study

Abstract: BackroundSugammadex is a reversal agent with well known advantages but it’s effects on haemostasis and bleeding have been a topic of interest. Septoplasty is a common surgical procedure with postoperative respiratory complications and bleeding. The aim of this study is to investigate the effects of sugammadex on postoperative coagulation parameters and bleeding after septoplasty procedure.Material/MethodsIn this randomized controlled study, fifty patients were grouped into two groups; neostigmine (Group N) vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Two studies reported no differences in the MAP of patients administered neostigmine and sugammadex; however, this was only in the neostigmine group, whereas the HR was lower at first and subsequently became higher [ 18 , 21 ]. Other studies determined that there were no significant differences in the HR and MAP for both agents [ 11 , 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported no differences in the MAP of patients administered neostigmine and sugammadex; however, this was only in the neostigmine group, whereas the HR was lower at first and subsequently became higher [ 18 , 21 ]. Other studies determined that there were no significant differences in the HR and MAP for both agents [ 11 , 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in the literature comparing the effects of sugammadex and neostigmine [ 8 , 13 , 18 , 19 ]. However, few of these studies were primarily designed to evaluate the effects of sugammadex and neostigmine on renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Despite transient (within 1 h) increases in APTT and PT in the sugammadex group, there was no increased risk of bleeding versus usual care. In another study of patients undergoing septoplasty, the authors evaluated the total amount of blood absorbed by the nasal dressings in the first 3 postoperative hours [ 72 ]. In this study, no statistically significant difference was found in PT and APTT values between the patients who received 2 mg/kg sugammadex and those who received neostigmine.…”
Section: Reviewmentioning
confidence: 99%
“…Regarding its clinical implication, no study has demonstrated evidence of increased bleeding risk after sugammadex use except 1 study. [ 11 ] Even the author of this study commented that increased bleeding that they found may associate with other uncontrolled factors rather than sugammadex. In line with previous studies, our study demonstrated that the amount of drain volume was similar in both sugammadex and pyridostigmine groups.…”
Section: Discussionmentioning
confidence: 89%
“…[ 12 , 16 ] Following clinical studies in surgical patients also reported the similar coagulation abnormalities. [ 10 , 11 ] Thus, according to the current drug supplementation, additional caution should be exercised when used in high-dose or in patients with high risk of bleeding. [ 17 ] Not only sugammadex may cause coagulation abnormality, but liver resection also causes PT prolongation because of consumptive or dilutional coagulopathy after hepatic resection.…”
Section: Discussionmentioning
confidence: 99%